Peran Perpustakaan di Era Digital Dalam Penguatan Akses Informasi - Muhammad Fariz Anaan; Lisa Agustina Soraya; Herlina (Perpustakaan Universitas Riau, 2025)
A library is a part of an educational establishment that supports learning, research, and publications by offering different types of information in accordance with user needs. Users nowadays have undergone a drastic transformation along with the quick growth of information and communications technologies. Starting with their Internet-based information-seeking habits, how they pick up knowledge while playing games or listening to music, and how much fun they have working together and exchanging information online. The term